The Influence of Service Quality, Taste, and Perceived Price on Customer Loyalty by Mediating Customer Satisfaction - M. Fikri Ashari; Zulkifli Musannip Efendi Siregar; Abd. Halim (Quantitative Economics and Management Studies, 2023)
This study aims to determine the effect of service quality, taste and price perceptions on customer loyalty through consumer satisfaction as a mediating variable. The population in this study were 100 populations of Mas Be geprek chicken customers. The sample in this study were 62 respondents with the purposive sampling technique used. The method used is the Quantitative Descriptive research method with data collection techniques in this study using a questionnaire in the form of a Google Form and distributed online via WhatsApp social media. The data analysis technique in this study is to use the SmartPLS SEM analysis method, with the media in data processing using the SmartPLS 3 program. The results of this study explain that Service Quality has no significant positive effect on Customer Satisfaction; Taste has a positive and significant effect on Customer Satisfaction; Price has a positive and significant effect on Customer Satisfaction; Service Quality has no significant positive effect on Customer Loyalty; Taste has a positive and significant effect on Customer Loyalty; Price has no significant positive effect on Customer Loyalty; And Customer Satisfaction as a mediation of Service Quality, Taste and Price has a positive effect on Customer Loyalty. Service Quality has no significant positive effect on Customer Loyalty; Taste has a positive and significant effect on Customer Loyalty; Price has no significant positive effect on Customer Loyalty; And Customer Satisfaction as a mediation of Service Quality, Taste and Price has a positive effect on Customer Loyalty. Service Quality has no significant positive effect on Customer Loyalty; Taste has a positive and significant effect on Customer Loyalty; Price has no significant positive effect on Customer Loyalty; And Customer Satisfaction as a mediation of Service Quality, Taste and Price has a positive effect on Customer Loyalty.